Kekosongan Hukum Pengaturan Sanksi Dalam Peraturan Kepala Daerah (Studi Kasus UU 12/2011 dan UU 23/2014) - Puspa Negara, I Nyoman; Edgar Tanaya, Putu (Kertha Wicara : Journal Ilmu Hukum, 2021)
This article aims to analyze the regulation of sanctions in the formation of Regional Head Regulations in Law 12/2011 and Law 23/2014 and to analyze the consequences of the legal vacuum in setting sanctions in the formation of Regional Head Regulations in Law 12/2011 and Law 23/2014. The research method used in writing this article is normative legal research. The regulation of sanctions in the formation of Regional Head Regulations In Law 12/2011 and Law 23/2014 are not clearly regulated and reflect a legal vacuum, where in Law 12/2011 it is stated that the content of criminal provisions can only be contained in laws, regulations and regulations. Provincial Region and Regency/City Regional Regulations. Meanwhile, Law 23/2014 only stipulates the provisions regarding the principle of formation and the content of the Perda applies mutatis mutandis to the principle of formation and the content of the Perkada. As a result of the legal vacuum in setting sanctions in the formation of regional head regulations in Law 12/2011 and Law 23/2014, it can create legal uncertainty or uncertainty in laws and regulations in the community, which will further result in legal chaos. Keywords: Legal Vacuum, Sanctions, Regional Head Regulations.